The Psychological Effects of Using Instagram: Its Effects on Anxiety, Self-Confidence, and Body Image - Collantes, Leonel Hernandez; Aulia Saputro, Nina; Akmaluddin, Rizky; Liliana, Shinta Ayu; Umam, Yogi Khairul; Harviansyah, Yushivan Rendi (Bulletin of Social Informatics Theory and Application, 2022)
Instagram has become a major social media platform that plays a big role in this modern society. People spend their time mindlessly scrolling through their Instagram feeds and it’s starting to affects their mental health, mostly on adolescents because they are going through a phase of finding their self-identity. The purpose of this research is to explore how Instagram affects mental healthiness in adolescents. It is focusing on the effects of Instagram on self-confidence, anxiety, and body image. To fulfill the purpose of this study, two types of research have been used according to the object study, descriptive and documentary research. The research design is non-experimental longitudinal, using the Instagram user experience survey as a measurement instrument to collect data and analyze the information. This research was conducted on 99 people from age 18 to 25 as the subject. The data collection was done by distributing the questionnaire for 7 days. As a result, this study shows that Instagram affects some users' psychological health in their anxiety, self-confidence, and body dissatisfaction.